OPTIMIZATION OF WIRELESS NETWORK PERFORMANCE USING THE HIERARCHICAL TOKEN BUCKET (CASE STUDY: MUHAMMADIYAH UNIVERSITY OF PALEMBANG) - Yukos Pratama; Usman Ependi; Heri Suroyo (Universitas Bina Darma, 2019)
Computer networks have penetrated into various fields including education for the learning process which is used as a medium for delivering scientific concepts to be more attractive and easily accepted. The Muhammadiyah University of Palembang currently has very high mobility, both used for browsing information, downloading data and using other facilities. For the need for bandwidth management to manage each passing data so that the distribution of bandwidth becomes evenly distributed by using the queue tree method that is applied to the proxy. To evaluate internet bandwidth analyze QoS (Quality of Service) using typhoid standardization in terms of measurement of throughput, delay, and packet loss. The results of this study show that the quality of the network with the hierarchical token bucket method is more optimal, this is because the bandwidth will be divided according to the rules applied to bandwidth management and does not cause clients to fight over bandwidth